Unraveling collaborative learning stimuli and effective dynamic capability integration on MNCs: the global capabilities administration model (GCAM) - Abrantes, B. F.; Preto, M. T.; António, N. (Review of International Business and Strategy, 2023)
Purpose: Dynamic capabilities yield positive effects to firm-specific advantage formation. Paradoxically, the body of literature on capability diffusion is scarce. The purpose of this study is to focus, thus, on this dearth of literature with an emphasis on exploring the transferability function. Design/methodology/approach: An integrative review of literature on the dynamic capabilities view covers the organizational context determining capability sharing, supported by strategic communication and business networking theories for the fashioning of global capabilities’ administration model (GCAM). Findings: Individual motivations and formal modelling of capabilities’ transference have been overlooked in previous research. Largely with a top-down orientation, the current paradigm of their diffusion is profoundly shaped by the organizational structure and its global governance practices. Research limitations/implications: The GCAM’s architecture, based on transnational administration and hybrid transferability, opens horizons for multinational companies to develop their own capability management systems and is at the same time a new scholarly avenue in the field. Originality/value: This study explores an untapped research gap and the formal modelling of a GCAM, while reconciling some of the weaknesses of academic research and industry practices.